2010
DOI: 10.1161/circheartfailure.110.945881
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Peri-Infarct Pacing Early After Myocardial Infarction

Abstract: Background-Left ventricular (LV) remodeling has been attributed to the segmental loss of viable myocardium due to myocardial infarction (MI), which results in redistribution of cardiac workload, with increased regional wall stress in and around the infarct zone. Because ventricular pacing has been shown to reduce regional wall stress and workload in regions near the pacing site, this trial was designed to test whether chronic pacing near the infarct attenuates LV remodeling. Methods and Results-Eighty patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Others have applied CRT to the post-MI rabbit heart without any conduction delay, and found benefits on chronic remodeling 20 . The use of PIZ-CRT was tested in post-MI patients with a narrow QRS 21 , though no effects on 1-year cardiac remodeling or clinical outcomes were found. However, these conditions differ from the present investigation in that we made pseudo-LBBB the baseline state.…”
Section: Discussionmentioning
confidence: 99%
“…Others have applied CRT to the post-MI rabbit heart without any conduction delay, and found benefits on chronic remodeling 20 . The use of PIZ-CRT was tested in post-MI patients with a narrow QRS 21 , though no effects on 1-year cardiac remodeling or clinical outcomes were found. However, these conditions differ from the present investigation in that we made pseudo-LBBB the baseline state.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 The Prevention of Myocardial Enlargement and Dilation Post Myocardial Infarction (MENDMI) study 21 and the Post-Myocardial Infarction Remodelling Prevention Therapy (PRomPT) trial 22 showed that pacing close to the infarcted area did not prevent LV dilatation or reduced heart failure hospitalization and/or all-cause mortality. The patients included in MENDMI and PROMPT differ significantly from the patients in the EchoCRT trial, who presented with more advanced LV remodelling and higher burden of LV myocardial scar/fibrosis.…”
Section: Interaction Between LV Gls and Crtmentioning
confidence: 99%
“…It is important to understand the effects of these cues if interventions are to be designed that seek to preserve cardiac function after infarction by controlling the anisotropy of infarct scar. Furthermore, many proposed therapies for myocardial infarction, such as injection of cells or polymers (Christman et al, 2004), implantation of materials for structural support (Kelley et al, 1999), and peri-infarct pacing (Chung et al, 2010) …”
Section: Resultsmentioning
confidence: 99%
“…We identified environmental factors and fibroblast behaviors that regulate anisotropy of infarct scar tissue and embedded this understanding in a computational framework that can be used to identify interventions that modify the properties of infarct scar for therapeutic benefit. Because a myriad of potential therapies for myocardial infarction are currently in development (Johnston et al, 2009;Chung et al, 2010;Morita et al, 2011;, we can use the model to anticipate unintended impacts of such interventions on the collagen fiber structure of infarct scar, and ultimately on heart function. This research has the potential to reduce the occurrence of heart failure and improve the quality of life of patients after myocardial infarction.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation